2022
DOI: 10.1111/acer.14786
|View full text |Cite
|
Sign up to set email alerts
|

Positive blood phosphatidylethanol concentration is associated with unfavorable waitlist‐related outcomes for patients medically appropriate for liver transplantation

Abstract: Background Excessive alcohol use is a leading etiology of liver disease and indication for liver transplantation. Accurate measurement of alcohol use remains a challenge in the management of patients in the pre‐, peri‐, and post‐liver transplant settings. Blood 16:0‐18:1 phosphatidylethanol (PEth) concentration is a sensitive and specific biomarker of binge and moderate, chronic alcohol use. As PEth has the longest detection window of available blood‐based direct alcohol biomarkers for moderate to heavy drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…PEth can be detected for up to 28 days from the last alcohol drink in patients with chronic alcohol use, whereas in patients with ALD who averaged 4 or more drinks per day, PEth was 96% specific for drinking within the last 30 days 42,43 . Unlike other biomarkers discussed here, PEth is not affected by age, gender, BMI, or severity of liver disease 16,43 . Given the PEth’s presence on erythrocytes, the replacement of a patient’s erythrocytes after a blood transfusion will decrease the reliability of that patient’s PEth results.…”
Section: Alcohol Metabolism: Direct and Indirect Biomarkermentioning
confidence: 82%
“…PEth can be detected for up to 28 days from the last alcohol drink in patients with chronic alcohol use, whereas in patients with ALD who averaged 4 or more drinks per day, PEth was 96% specific for drinking within the last 30 days 42,43 . Unlike other biomarkers discussed here, PEth is not affected by age, gender, BMI, or severity of liver disease 16,43 . Given the PEth’s presence on erythrocytes, the replacement of a patient’s erythrocytes after a blood transfusion will decrease the reliability of that patient’s PEth results.…”
Section: Alcohol Metabolism: Direct and Indirect Biomarkermentioning
confidence: 82%
“…19 One recent study showed that the availability of PEth testing at a LT center resulted in a higher rates of LT evaluation termination or de-listing, while another reported that positive PEth tests were associated with unfavorable LT waitlist outcomes. 20,21 Quality improvement (QI) is an important cornerstone of LT programs as centers seek to continually improve processes of care and patient outcomes. 22,23 A recent national survey showed that most programs do not have alcohol screening protocols in the post-LT setting despite widespread monitoring in the pre-LT setting, making this an ideal target for a QI initiative.…”
Section: Introductionmentioning
confidence: 99%
“…PEth can detect alcohol ingestion up to 3 weeks prior with heavy use and levels do not vary with age, sex, liver or kidney function 19 . One recent study showed that the availability of PEth testing at a LT center resulted in a higher rates of LT evaluation termination or de‐listing, while another reported that positive PEth tests were associated with unfavorable LT waitlist outcomes 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the window of detection of alcohol use and accuracy of biomarkers vary based on the amount of alcohol consumed by the individual and the cut-off used to adjudicate abnormal test results. Although a promising biomarker, data on PEth use in LT centers remain limited.In the April issue of this journal, Faulkner et al report on a retrospective study that examined the association of positive PEth results (≥20 ng/dL) with waitlist outcomes among patients either listed or being evaluated for LT(Faulkner et al, 2022). Whole blood was tested for PEth levels and the waitlist outcomes were studiedfor a period of 7 to 259 days from the date of PEth testing.…”
mentioning
confidence: 99%
“…In the April issue of this journal, Faulkner et al report on a retrospective study that examined the association of positive PEth results (≥20 ng/dL) with waitlist outcomes among patients either listed or being evaluated for LT (Faulkner et al, 2022). Whole blood was tested for PEth levels and the waitlist outcomes were studied for a period of 7 to 259 days from the date of PEth testing.…”
mentioning
confidence: 99%